Similar and dissimilar resistance spot weldability of galvanised DP1000 and TWIP980 steels. (19th May 2017) - Wei, S. T.; Lv, D.; Liu, R. D.; Lin, L.
ABSTRACT: Similar and dissimilar combinations of a 1000 MPa galvanised dual phase (DP) steel and a 980 MPa twining-induced plasticity (TWIP) steel were resistance spot welded under different welding parameters. The microstructure, expulsion situation, nugget size and mechanical properties of spot welds were evaluated systematically. The results showed that the differences of microstructure and chemical compositions caused that the weld nugget hardness increases in the order of TWIP/TWIP, DP/TWIP and DP/DP. The lower melting point and heat conductivity of the TWIP steel and the lower electric resistance of the zinc coat on the DP steel caused that the expulsion occurring current increased in the order of TWIP/TWIP, DP/TWIP and DP/DP and under the same welding condition the nugget diameter increased in the order of DP/DP, DP/TWIP and TWIP/TWIP. Furthermore, the tensile shear failure mode and location depends on the nugget size, microstructure and hardness distribution of spot weld.